ANALISIS KADAR SERAT PADA NUGGET BATANG LENGKUAS MUDA (Alpinia galanga L) SEBAGAI PENUNJANG SUMBER BELAJAR MATA KULIAH ETNOBOTANI - Titdoy, Nia Rusfita; Watuguly, Theopilus W; Tuapattinaya, Prelly M.J (Program Studi Pendidikan Biologi FKIP Unpatti, 2021)
Background: Indonesia is a country rich in various types of plants, including spices. One of them is galangal [Alpinia galanga (L.) Swartz.] Which is often used by Indonesians as a cooking spice. This plant of the Zingiberaceae family has active substances that function to treat digestive disorders, relieve colic, as an antidote to poisoning, anti convulsions and has anti-arthritis activity. Galangal rhizome extract also has anticancer and anti-tuberculosis activity. Methods: The location for crude fiber testing was carried out at the Ambon Industrial Research and Standardization Center (Baristand). Young galangal stems are taken at Jl. Mount Malintang, Batu Merah, Sirimau, Ambon City Maluku. This research is a descriptive study with a qualitative approach. Results: The results showed that crude fiber content in young galangal stem nuggets in P3 with a ratio of 2: 1 resulted in crude fiber content of 2.62% higher than young galangal stem nuggets at P2 with a ratio of 1: 2 resulting in crude fiber content of 0 , 52% and young galangal stem nuggets at P1 with a ratio of 1: 1 resulted in crude fiber content of 1.46%. Conclusion: Crude fiber content with different ratios obtained P1 (1.46%), P2 (O, 52%), P3 (2.62%).